2012
DOI: 10.1073/pnas.1202056109
|View full text |Cite
|
Sign up to set email alerts
|

Nonconscious activation of placebo and nocebo pain responses

Abstract: The dominant theories of human placebo effects rely on a notion that consciously perceptible cues, such as verbal information or distinct stimuli in classical conditioning, provide signals that activate placebo effects. However, growing evidence suggest that behavior can be triggered by stimuli presented outside of conscious awareness. Here, we performed two experiments in which the responses to thermal pain stimuli were assessed. The first experiment assessed whether a conditioning paradigm, using clearly vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
224
3
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 262 publications
(253 citation statements)
references
References 45 publications
20
224
3
6
Order By: Relevance
“…Our experiment included both subliminal (unseen) and supraliminal (seen) conditioned stimuli and found no significant difference in outcomes between the two. In a previous study (20), we provided evidence for nonconscious activation of analgesic and hyperalgesic responses established with supraliminal stimuli during an earlier conditioning phase. Thus, we extend our previous findings by demonstrating that new learning of conditioned pain responses can occur even when the conditioned stimulus is presented subliminally during the acquisition phase.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Our experiment included both subliminal (unseen) and supraliminal (seen) conditioned stimuli and found no significant difference in outcomes between the two. In a previous study (20), we provided evidence for nonconscious activation of analgesic and hyperalgesic responses established with supraliminal stimuli during an earlier conditioning phase. Thus, we extend our previous findings by demonstrating that new learning of conditioned pain responses can occur even when the conditioned stimulus is presented subliminally during the acquisition phase.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have reported that conditioning procedures for physiological functions that can be consciously perceived (e.g., pain reduction) are mediated by expectancy compared with responses that are not consciously perceptible (e.g., hormone release) (7,10). How can we reconcile the apparent difference in outcomes between studies indicating that conditioned placebo and nocebo analgesia responses are mediated by expectancy and our data showing that conditioned analgesic and hyperalgesic responses can be acquired and activated with cues that are not consciously perceived (20,24)? We believe that the answer may lie in differences between conditioning procedures.…”
Section: Discussionmentioning
(Expert classified)
See 2 more Smart Citations
“…These curious responses are not entirely dependent on conscious perception of cues since they may be generated by unconscious cues as well (Jensen et al, 2012).…”
Section: Neurobiology Of Negative Expectationsmentioning
confidence: 99%